The impact of the private security industry on peace-building efforts in Africa : an assessment of Executive Outcomes, MPRI and DynCorp - Holager, Emma (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2011.